ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KOTA BATAM - Hayati, Sthevannie Akbarinabi; Br Purba, Neni Marlina (LPPM Universitas Putera Batam, 2024)
This study aims to determine the factors that influence motor vehicle tax compliance in Batam City. This research consists the variables of Taxpayer Understanding, Taxpayer Awareness, Service Quality, and Tax Sanctions on Taxpayer Compliance. The population in this research are all taxpayers vehicle registered in the office of SAMSAT Kota Batam until 2022 that as many as 442.092 vehicles. The samples used of 150 respondents. This study uses quantitative data types, the data source uses primary data with data collection techniques is by distributing questionnaires. The data analysis technique is validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression, hypothesis test, partial test, F test, and coefficient of determination. Data processing technique used SPSS software version 27. Based on research, concluded that Taxpayer Understanding and Taxpayer Awarenes not have significant influence on Taxpayer Compliance, however Service Quality and Tax Sanctions show significant influence. However, together all the variable show an influence on taxpayer compliance. The coefficient of determination of 0.140 indicates that variables Taxpayer Understanding, Taxpayer Awareness, Service Quality, Tax Sanctions have influence of 14% on Taxpayer Compliance while the remainder 86.0 % is explained by other variables outside the independent variables contained in this study.